Impact of the rating system on sentiment and tone of voice: A Booking.com and TripAdvisor comparison study - Rita, Paulo (2022)
Rita, P., Ramos, R., Borges-tiago, M. T., & Rodrigues, D. (2022). Impact of the rating system on sentiment and tone of voice: A Booking.com and TripAdvisor comparison study. International Journal of Hospitality Management, 104, 1-12. [103245]. https://doi.org/10.1016/j.ijhm.2022.103245 ----- Funding Information: Paulo Rita was supported by FCT ( Fundação para a Ciência e a Tecnologia ) under UIDB/04152/2020 — Centro de Investigação em Gestão de Informação (MagIC).